The First Triangular Representation of The Symmetric Groups when n=6 (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this paper, we study a special case of the first triangular representation of the symmetric groups when n=6 over a field K of characteristic p.